ANALYSIS OF THE EFFORTS OF THE COOPERATIVE OFFICE IN INCREASING MSME INCOME (CASE STUDY ON THE COOPERATIVE AND UMKM OFFICE OF BINJAI CITY) - Rizky Pratama, Muhammad; Amalia, Alfi (Universitas Islam Lamongan, 2024)
MSMEs in Binjai City are the backbone of the regional economy with various business sectors, ranging from trade, services, to creative industries. The Binjai City Cooperatives and MSMEs Department has an important task in encouraging the growth and sustainability of MSMEs in this region. This research aims to identify and analyze the efforts that have been made by the Cooperatives Department to increase MSME income, as well as identify the obstacles faced in its implementation. This research uses qualitative research methods with a descriptive approach. The results of this research state that the Binjai City Cooperative Department’s efforts to increase MSME income include a comprehensive and sustainable strategy, which includes managerial training, access to financing, market development and technological innovation. The obstacles faced by the Binjai City Cooperative Department in increasing MSME income reflect complex structural and operational challenges, including limited access to financing, knowledge and skills gaps, and inadequate infrastructure. To overcome this, the Cooperatives Service has implemented various strategies, such as expanding access to financing through collaboration with microfinance institutions, increasing financial management and digital marketing training programs, as well as improving infrastructure and opening new market access.